2016
DOI: 10.1111/jdi.12468
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cell glutamate signaling: Its role in incretin‐induced insulin secretion

Abstract: Insulin secretion from the pancreatic β‐cell (referred to as β‐cell hereafter) plays a central role in glucose homeostasis. Impaired insulin secretion is a major factor contributing to the development of diabetes and, therefore, is an important target for treatment of the disease. Cyclic adenosine monophosphate is a key second messenger in β‐cells that amplifies insulin secretion. Incretins released by the gut potentiate insulin secretion through cyclic adenosine monophosphate signaling in β‐cells, which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
(62 reference statements)
0
10
0
3
Order By: Relevance
“…PKA has numerous targets involved in recruitment and fusion of insulin granules to the membrane (133,134). Gheni et al identified cytosolic β-cells glutamate as an essential signal mediating incretin-induced potentiation of insulin secretion in rodents models of diabetes, obesity and in insulin-producing cell lines (109,135). Incretin signalling induced the loading of glutamate into secretory granules, which was subsequently necessary for enhanced insulin release.…”
Section: β-Islet Cell Glutamate Transporters Vglut (Slc17 Family)mentioning
confidence: 99%
“…PKA has numerous targets involved in recruitment and fusion of insulin granules to the membrane (133,134). Gheni et al identified cytosolic β-cells glutamate as an essential signal mediating incretin-induced potentiation of insulin secretion in rodents models of diabetes, obesity and in insulin-producing cell lines (109,135). Incretin signalling induced the loading of glutamate into secretory granules, which was subsequently necessary for enhanced insulin release.…”
Section: β-Islet Cell Glutamate Transporters Vglut (Slc17 Family)mentioning
confidence: 99%
“…Additionally, we found significant enrichment of band a-cell gene sets involved in specific developmental signaling pathways. However only a subset of these pathways, like mTOR, retinoic acid receptor, glutamate receptor and TGF-b signaling, have been previously linked to b-and a-cell biology [72][73][74][75] The cost basis of pancreas procurement and islet isolation from pigs is currently lower than for humans. In 2019, reimbursement for a single human cadaveric donor pancreas is between $4,500 and $7,000 (US dollars).…”
Section: Discussionmentioning
confidence: 99%
“…26 Yapılan çalışmalara göre, yanıtın büyüklüğü sitozolik serbest Ca 2+ 'nın 500 nM'den 1,3 μM'ye yükselmesine benzerdir. 27 Α-ketoglutarat, malat veya sitrat gibi TCA döngüsünün ara maddeleri, insülin sekresyonunda anlamlı bir artışa neden olmamıştır. İnsülin salınımının uyarılması hem TCA döngüsüne karbon tedarik etmeyi hem de mitokondriyal Ca 2+ seviyelerini artırmayı gerektirmektedir.…”
Section: İnsüli̇n Sekresyonunda Glutamatin Rolüunclassified
“…Bu iki durum da süksinat ile sağlanmaktadır. 26,27 İzole edilmiş INS-1 hücre mitokondrisinin süksinata maruz kalmasının, önemli miktarda glutamat üretmesine neden olduğu bildirilmiştir. Mitokondrideki glutamat, glutamat dehidrogenaz enzimi aracılığıyla TCA döngüsündeki α-ketoglutarattan üretilmektedir.…”
Section: İnsüli̇n Sekresyonunda Glutamatin Rolüunclassified
See 1 more Smart Citation